The HR manager who proved his worth. Issue 2 (16th April 2015) - Gopinath, Mohan; Abraham, Dolphy; Prabhakaran, Asha
Abstract : Subject area: Organizational ethics and related issues. Study level/applicability: Graduate course on Strategic Human Resource Management and specialization courses in Banking. Case overview: This case details the account of a human resources (HR) manager of a multinational bank in India who "used" his position to bring on board his cronies to secure his position and utilize the inherent powers in the position to further his own ends. The case elaborates how the Manager HR went about his job soon after taking over and the consequences this had on the Indian operations and the morale of officers. The case requires the students to analyze and suggest ways in which this organization can prevent such occurrences in future. Expected learning outcomes: The primary learning objective is to help the student understand the significance of organizational ethics values and react to issues arising from dealing with unethical practices. It will also make them aware of what can happen if systems are deliberately flouted and reporting protocol relating to information flows are ignored. Specifically, it will help them to select the right people, who are aware of the culture of the organization and what this culture implies in terms of working ethically. Communicate the working standards expected of its employees, especially newly trained ones. Analyze the challenges an employee can face when he or she tries to do things in the organization which are not ethical. Evaluate the different ways in which errant employees should be handled. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.